Interesting Cytokine Profile Caused by Clinical Strains of Pseudomonas aeruginosa MDR Carrying the exoU Gene - Nallely S. Badillo-Larios; Edgar Alejandro Turrubiartes-Martínez; Esther Layseca-Espinosa; Roberto González-Amaro; Luis Fernando Pérez-González; Perla Niño-Moreno (International Journal of Microbiology)
Pseudomonas aeruginosa is an opportunistic pathogen in HAIs with two facets: the most studied is the high rate of antimicrobial resistance, and the less explored is the long list of virulence factors it possesses. This study aimed to characterize the virulence genes carried by strains as well as the profile of cytokines related to inflammation, according to the resistance profile presented. This study aims to identify the virulence factors associated with MDR strains, particularly those resistant to carbapenems, and assess whether there is a cytokine profile that correlates with these characteristics. As methodology species were identified by classical microbiological techniques and confirmed by molecular biology, resistance levels were determined by the minimum inhibitory concentration and identification of MDR strains. Virulence factor genotyping was performed using PCR. In addition, biofilm production was assessed using crystal violet staining. Finally, the strains were cocultured with PBMC, and cell survival and the cytokines IL-1β, IL-6, IL-10, IL-8, and TNF-α were quantified using flow cytometry. Bacteremia and nosocomial pneumonia in adults are the most frequent types of infection. In the toxigenic aspect, genes corresponding to the type III secretion system were present in at least 50% of cases. In addition, PBMC exposed to strains of four different categories according to their resistance and toxicity showed a differential pattern of cytokine expression, a decrease in IL-10, IL-6, and IL-8, and an over-secretion of IL-1b. In conclusion, the virulence genes showed a differentiated appearance for the two most aggressive exotoxins of T3SS (exoU and exoS) in multidrug-resistant strains. Moreover, the cytokine profile displays a low expression of cytokines with anti-inflammatory and proinflammatory effects in strains carrying the exoU gene.